Hybrid genetic hill-climbing algorithm for four-colouring map optimisation - Lim, Heng Won. (2008)
The objective of an n-region 4-colouring map problem is to colour the regions in the map such that the adjacent regions (sharing a common boundary) are coloured differently to distinguish the different regions and complete the colouring in the shortest (computation) time possible.